2015
DOI: 10.1186/s12882-015-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Astragaloside IV attenuates proteinuria in streptozotocin-induced diabetic nephropathy via the inhibition of endoplasmic reticulum stress

Abstract: BackgroundDiabetic nephropathy (DN) is a major cause of Chronic Kidney Disease and End-Stage Renal Disease throughout the world; however, the reversibility of diabetic nephropathy remains controversial. Endoplasmic reticulum (ER) stress plays an important role in the pathogenesis of DN. Astragaloside IV (AS-IV) is derived from Astragalus membranaceus (Fisch) Bge, a widely used traditional herbal medicine in China, and has diverse pharmacological activities including the attenuation of podocyte injury and ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 38 publications
4
60
0
Order By: Relevance
“…GRP78 (BiP) is a 78-kDa protein chaperone [26,27] that has been proven to prevent the cell death caused by disturbance of endoplasmic reticulum (ER) homeostasis [28] and to mediate essential components of ER stress-induced apoptosis [31][32][33]. Fluorescent labeling and immunofluorescence staining indicated that TTR efficiently crossed cell membrane and nuclear membrane; the localization of TTR and GRP78 partially overlapped in and around the nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…GRP78 (BiP) is a 78-kDa protein chaperone [26,27] that has been proven to prevent the cell death caused by disturbance of endoplasmic reticulum (ER) homeostasis [28] and to mediate essential components of ER stress-induced apoptosis [31][32][33]. Fluorescent labeling and immunofluorescence staining indicated that TTR efficiently crossed cell membrane and nuclear membrane; the localization of TTR and GRP78 partially overlapped in and around the nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…mongholicus (Bge.) Hsiao and has various pharmacological activities, including anti-tumor, anti-inflammatory and anti-diabetic (3,4). Curcumin (diferuloylmethane) is the chief component of the spice turmeric and is derived from the rhizome of the East Indian plant Curcuma longa.…”
Section: In Combination Significantly Reduced Mean Tumor Weight Compamentioning
confidence: 99%
“…Though we successfully established a mice model with nephropathy and observed the upregulated GRP78 and CHOP in this model, we were not able to directly prove that ER stress did participate in the renal lesion of diabetes. Some study has proved that ER stress contributed to the renal injury in diabetic rats induced by STZ 10,21,22 , thus we conjecture that both models share the same mechanism on the onset of DN. We believe that this mechanism on DN can be explored by inhibiting the ER stress using an ER stress inhibitors such as 4-phenylbutyric acid (4-PBA).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has revealed that ER stress contributed to insulin resistance, aggravated β-cell burden, and reduced β-cell mass, resulting in T2DM 9 . Though two recent studies have proved that ER stress is activated in the kidney of diabetic rats 10,11 , whether ER stress influences renal tissue in Kunming (KM) mice treated with high-fat diet and streptozotocin (STZ) is poorly understood. In this study, we aim to test whether renal lesion occurs in the diabetic Kunming mice induced by combination of high-fat diet and STZ.…”
Section: Introductionmentioning
confidence: 99%